2002
DOI: 10.1086/502024
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Nosocomial Transmission of Pulmonary Tuberculosis: When may Isolation be Discontinued for Patients with Suspected Tuberculosis?

Abstract: Unless there is high clinical suspicion of pulmonary TB in a specific patient, the use of three AFB smears on expectorated sputa is a rational approach to discontinuing isolation for patients with suspected TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The percentages of patients in these studies, identified as AFB smear positive by at least the third specimen alone, were 0%, 5.3%, 8.6% and 11.1% (1,2,7,8). Two of these studies endorsed change to a two-smear approach for discontinuing isolation based on their findings, while the other two recommended continuing a three-smear approach (1,2,7,8). The present study identified 3.2% of patients on at least the third smear, which supports a two-smear approach as sufficient for discontinuing respiratory isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of patients in these studies, identified as AFB smear positive by at least the third specimen alone, were 0%, 5.3%, 8.6% and 11.1% (1,2,7,8). Two of these studies endorsed change to a two-smear approach for discontinuing isolation based on their findings, while the other two recommended continuing a three-smear approach (1,2,7,8). The present study identified 3.2% of patients on at least the third smear, which supports a two-smear approach as sufficient for discontinuing respiratory isolation.…”
Section: Discussionmentioning
confidence: 99%
“…This expanded RI policy for all patients suspected of PTB in the United States led to the proper isolation of over 95% of PTB upon admission; however, it also resulted in an 8-fold overuse of the isolation room, and eventually led to an insufficient number of isolation rooms [7]. Under the threatening of acute lung disease such as the severe acute respiratory syndrome (SARS) virus and the new H1N1 influenza nowadays, a 3-day isolation policy for waiting times for smear results for all patients merely suspected of active PTB, may prove too burdensome for most hospitals [8,9]. Furthermore, an isolation policy based solely upon negative sputum samples may not adequately account for the truly positive sputums missed due to low organism loads [10].…”
Section: Introductionmentioning
confidence: 99%
“…Acid‐fast staining is a simple and inexpensive method; however, there always exists the possibility of obtaining false results (Siddiqui et al . ; Masood et al . ).…”
Section: Introductionmentioning
confidence: 96%
“…Currently used TB diagnostic tests include the conventional acid-fast staining, mycobacterial culture and nucleic acid amplification. Acid-fast staining is a simple and inexpensive method; however, there always exists the possibility of obtaining false results (Siddiqui et al 2002;Masood et al 2008). Although fluorescence staining could improve the test sensitivity and efficiency, misdiagnosis caused by autofluorescent artefacts may occur (Thakur et al 2013).…”
Section: Introductionmentioning
confidence: 99%